User’s Perspective of Eletronic Government Adoption in Brazil‌ - Salati Marcondes de Moraes,Gustavo Hermínio (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2017)
The objective of this work was to study which factors influence the use of e-government in Brazil, focusing on investigating government computerization initiatives of fiscal control mechanisms, through a study on the Nota Fiscal Paulista program. We interviewed approximately 3,500 citizens who have used the program, in 11 cities in the State of São Paulo. Of this total, 715 responses were considered valid. We used a quantitative methodology for the development of this research, through the multivariate analysis technique of structural equation modeling. The study presented a robust model with a high explanatory power, in which the influencing factors are: Perceived Benefit; Perceived Ease of Use; Social Influence; Perceived Security; Trust in the Government and Habit.